MULTIPLICATION IN VITRO OF MARUBAKAIDO APPLE ROOTSTOCK ON DIFFERENTS CULTURE MEDIA AND GIBBERELLIC ACID CONCENTRATIONS - MACHADO, Marília Pereira; de CARVALHO, Dayse Cristina; BIASI, Luiz Antonio (Scientia Agraria, 2004)
The rootstock Marubakaido is very used for the procuction of apple plantlet and has been multiplied in vitro for the production of elite plants. The micropropagation protocol can be more efficient, with the increase of the number of longer shoots in the multiplication phase. The objective of the experiment was to test the effect of the culture medium double-phase and concentrations of gibberellic acid (GA3) in the multiplication of this cultivar. The experimental design was a randomized complete block in a 2x3 factorial scheme two types of media (medium semisolid and douple-phase) and three concentrations of GA3 (0, 1 and 5 ì M), with five replications, with five shoots in each vessels with four vessels in each replication. Two subcultivations had been evaluated, with interval of forty five days. The analyzed parameters had been the number of shoots for explant, height of the shoots and the cool mass of shoots. Interaction between the studied factors did not occur. The culture medium double-phase presented best to the culture medium semisolid in all the parameters analyzed in the two subcultivos. The explants cultivated in the medium double-phase had formed higher shoots, in largest number and with largest cool mass. The GA3 did not present the waited effect of allonge of the shoots. For the multiplication of the rootstock of apple Marubakaido use of the culture medium double-phase is recommend, not being necessary the GA3 addition.